Dynamic light back-scattering with polarization gating and Fourier spatial filter for particle sizing in concentrated suspension - Hui, Yang; Gang, Zheng; Shu-guang, Dai; Ren-jie, Zhang; Ping-an, Mu (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
We present here a new dynamic light scattering method for investigating the particle size in concentrated suspension. By using the polarization gating and Fourier spatial filter, the optical thickness through the sample is reduced and the multiple scattered light is suppressed. The method is systematically tested using suspensions of latex spheres of 100 nm with a wide range of concentrations. Compared to the current common methods for nanoparticle sizing in concentrated suspension, it has the advantage of simple structure and it is easy to debug and maintain.
Optica Applicata, Vol. 40, 2010, nr 4, s. 819-826
Keywords: optyka; particle sizing; dynamic light scattering (DLS); back-scattering; polarization gating; Fourier spatial filter